Fenomen narracji litanijnej wobec stereotypu gatunkowego litanii - Sadowski, Witold (Wydawnictwo Naukowe UAM, 2009)
The article describes the phenomenon of narration in the litany, where the specific events are presented as units of the divine plan in the superior and impenetrable order, accepted by the compiler of the prayer. The phrases describing the events do not link together in a consecutive chain, but are interrupted by the repeated formulae of the prayer, on which they depend syntactically. According to this, the text of the litany does not report the holy story from anyone’s point of view. Each event undergoes the substantialization, it acquires a value, and its description can be used as an epithet or a periphrasis of the name of God, Virgin Mary, the angel or the saint. The story should be independent of the time, and the experience of the holy event is to be accessible to the faithful. Sometimes the story needs not to be explicated, because the text of the litany is already embedded in the ‘hermeneutic sphere’ (the term by S. Balbus) of the litanic genre. The technique of the narration in litany has been taken over by the poetry. The example of Jarosław Iwaszkiewicz’s epilogue to the poem Jeszcze jedna podróż (One more journey) published in 1963 is presented in the article. Znaczna
The phenomenon of narration in the litany and the genre stereotype of litany